Determinants of dietary adequacy among school age children in Guraghe Zone, Southern Ethiopia - Abdu Oumer Abdu; Berhanu Abebaw Mekonnen (International Journal of Public Health Science (IJPHS), 2019)
Dietary diversity (DD) is a validated proxy indicator of micronutrient adequacy among different age groups including infants, children and women. This study assessed level of dietary adequacy and its associated factors among school age children in Guraghe Zone, Ethiopia. Survey was conducted among 769 children aged 6 to 12 years of with their care givers using multistage sampling method. Data were collected by using structured questionnaire containing the ten food groups for minimum dietary diversity for women and other parts. Adequate dietary diversity was categorized those children who consume at least five food groups. Bivariate and multivariable binary logistic regression with odds ratios (95% CI) was computed. Overall 769 children were included in the study, with a mean age of 8 years. The mean dietary diversity score was 4.9 (±1.42). About 444 (58.3%) had an inadequate dietary diversity. Those children from extended family size had 1.3 times to have inadequate DD level (AOR=1.3). Children from female headed households, did not attend formal education had 1.3 and 1.4 times higher odds of having an inadequate DD level (AOR=1.3 and 1.4). Similarly, children living with uneducated caregiver had six fold more likely to have an adequate DD level (AOR=6.7). The dietary diversity of children in the study area was below average. Household head, caregiver’s educational status, occupation of the household head, father/female headed household and family size were found to be associated with DD score. There should be awareness creation through existing Health extension platform and back yard vegetation should be improved.